A Single Dose of Oral Sucrose Is Enough to Control Pain During Venipuncture: A Randomized Controlled Trial - Cavicchiolo, Maria Elena; Daverio, Marco; Battajon, Nadia; Frigo, Anna Chiara; Lago, Paola (Frontiers in Pain Research, 2022)
Sucrose is effective in reducing pain during minor procedures in neonates. We evaluated whether a second dose of sucrose was more effective than a single dose during venipuncture. We performed a randomised, double-blind, controlled trial at the NICU of Padua Hospital(August 2016-October 2017). We randomised 72 preterm infants undergoing venipuncture for routine test to a control group, which received a single standard dose of sucrose 2' before the procedure and a placebo 30" after the venipuncture, and an experimental group in which they received two doses of 24% sucrose 2' before and 30" after the venipuncture. No difference in pain perception was found between the groups at 30", 60" and 120". In conclusion,we do not recommend a second dose of sucrose during venipuncture in prematures.